Translating Cultural Difference: Fakir Mohan Senapati's Chha Mana Atha Guntha - St-Pierre, Paul (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1997)
AbstractThe analysis of four translations into English of the late nineteenth-century Indian (Oriya) novel Chha Mana Atha Guntha (literally: Six Acres and Thirty-Two Decimals) shows that translators, faced with references to specific aspects of the source culture, may use a variety of tactics, including non translation, as a part of their overall strategy. The choices translators make not only result in a new text but also construct a new readership, and these choices, texts, and readerships can and do vary. The differences between the translations examined reflect the complexity involved in the translation into English, the language of the former colonial power, of Indian-language texts, and the diverse ways in which these languages can reinvent their relations in a postcolonial context.